Effect of Job Stress, Job Competence and Job Training on Employee Performance at PT Indostar Sukses Mandiri Medan - Dennis Swarant; Kristi Endah Ndilosa Ginting (Institute of Computer Science (IOCS), 2021)
This research was conducted at PT Indostar Sukses Mandiri Medan. The purpose of this study was to examine and analyze the effects of Job Stress, Job Competence and Job Training on Employee Performance at PT Indostar Sukses Mandiri Medan. The research method uses quantitative. Population and sample amounted to 63 employees. The sampling technique used was saturated sampling. The results of the calculation of the partial hypothesis testing obtained tcount> ttable or 3.172> 2.001 and the significant obtained was 0.002 <0.05, meaning that Ho was rejected and Ha was accepted, that is, Job Stress partially affected Employee Performance at PT Indostar Sukses Mandiri Medan The results of the calculation of the hypothesis testing partially and simultaneously Job Stress.